Behavioral Effects of Opioid Full and Partial Agonists During Chronic Buprenorphine Treatment - Withey, Sarah L; Spealman, Roger D; Bergman, Jack; Paronis, Carol A (The Journal of pharmacology and experimental therapeutics, 2019)
Buprenorphine, a partial agonist at the -opioid receptor, is commonly prescribed for the management of opioid addiction. Notwithstanding buprenorphine's clinical popularity, the relationship between its effectiveness in attenuating relapse-related behavior and its opioid efficacy is poorly understood. Furthermore, changes in the antinociceptive potency or effectiveness of opioid drugs that might occur during buprenorphine treatment have not been characterized. Here, we address these questions by assessing the ability of daily buprenorphine treatment to protect against the reinstatement of drug-seeking behavior by six opioids differing in efficacy (methadone, heroin, oxycodone, buprenorphine, butorphanol, nalbuphine) and, in separate experiments, by determining how such treatment may modify their antinociceptive effects. In one set of experiments, squirrel monkeys were trained to respond under concurrent schedules (choice) of food or intravenous oxycodone presentations. The priming strength of different opioids during sessions in which saline, rather than oxycodone, was available for intravenous self-administration was determined before and during chronic buprenorphine treatment (0.1 or 0.32 mg/kg per day). In other subjects, antinociceptive effects of the different opioids were assessed using cumulative dosing procedures in a modified warm-water tail withdrawal procedure before and during buprenorphine treatment. Results show that, notwithstanding some tolerance, full agonists retain high efficacy in producing priming and antinociceptive effects. In contrast, both the priming strength and antinociceptive effectiveness of partial agonists were decreased. These results suggest that the utility of buprenorphine in the management of opioid addiction, and how it alters the analgesic effects of opioids, can vary depending on the efficacy of the abused or prescribed opioid. SIGNIFICANCE STATEMENT: Our findings indicate that the pharmacological efficacy of abused opioids may predict the ability of buprenorphine to attenuate their relapse-related priming and analgesia-related antinociceptive effects. This information can help inform physicians as to the effectiveness and limitations of buprenorphine as a pharmacotherapy for opioid addiction.